Pertanggungjawaban Pemerintah Terhadap Mahasiswa Indonesia Korban Eksploitasi Program Magang Ferienjob di Jerman - Nurfajriana, Syifa; Prasetyo, Handoyo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Universities must design innovative learning to optimize student attitudes, knowledge, and skills. One of them includes the internship program at the Merdeka Campus. However, some parties abuse this situation resulting in the exploitation of students in the Ferienjob Internship Program in Germany. The aim of this research is to determine the government's responsibility towards students in the Ferienjob Internship Program in Germany. The research method used is normative research. This criminal act of human trafficking (TPPO) began with the socialization of the Ferienjob program at various universities by PT Cvgen and PT Sinar Harapan Bangsa (SHB). The perpetrators attract potential participants with tempting promises, such as stating that this internship program equals 20 college credits. The human trafficking case has involved several parties, both the government and the target company, so the government must be responsible for providing protection to the victims. The criminal act of trafficking in persons (TPPO) involves many parties, and students are exploited economically and energetically, so the government has a big responsibility to provide adequate protection. The author suggests that the government immediately develop special regulations for international internship programs for vocational and non-vocational students.